Relationship between washing ratio and chromatic aberration. Issue 3 (14th March 2020) - Ding, Xuemei; Shao, Fenjuan; Han, Yutong; Wu, Xiongying
Abstract : Purpose: Denim, a common fade fabric, can present different degrees of fade under different washing conditions. The phenomenon is similar to the washing efficiency. This study aims to discuss the relationship between impact factors and washing efficiency as well as the color fastness. Design/methodology/approach: JMP software was used to design different experiments and 40 experimental groups were obtained. Then Statistical Package for the Social Sciences was used to analyze the results about washing efficiency and chromatic aberration. Findings: Results showed that washing temperature, washing time and rotation speed have an effect on color fastness after washing in turn. In a certain range, when washing temperature, washing time or rotation speed increases, color fastness gradually increases as well. These three washing parameters work on washing efficiency as well. After setting and analyzing the mathematical model, the R² between the three washing parameters and washing efficiency is 0.855 and the R ² between the three washing parameters and the post-wash chromatic is 0.849. There is a correlation between "Washing Efficiency of Sebum RM (P)" and "Post-wash Chromatic aberration (Q)". Practical implications: Denim could be used in some tests in laboratories instead of sebum standard stain cloth. Originality/value: This paper provides an indirect research and feasible method for exploring a new object instead of the standard pollution cloth in the test of related textile study in the future.